14.6k views
4 votes
Choose the property used to rewrite the expression. log618-log66 = log63.a) Commutative Propertyb) Product Propertyc) Power Propertyd) Quotient Property

User Titogeo
by
6.0k points

1 Answer

1 vote

Answer:

Option d) is correct

ie, quotient property

Explanation:

Given expression is log 618-log 66=log 63

Now we take log 618-log 66

log 618-log 66 = log
(618)/(66) [By using quotient property, log
(x)/(y)=\log x- \log y]

= log 63

Therefore log 618- log 66= log 63

Option d) is correct

In the given expression we are using the quotient property

User A Fader Darkly
by
6.5k points